Temporal LiDAR scanning in quantifying cumulative rockfall volume and hazard assessment: A case study at southwestern Saudi Arabia - Abdullah A. Alotaibi; Norbert H. Maerz; Kenneth J. Boyko; Ahmed M. Youssef; Biswajeet Pradhan (Egyptian Journal of Remote Sensing and Space Sciences, 2022)
Rockfalls and unstable slopes pose a serious threat to people and property along roads/highways in the southwestern mountainous regions of Saudi Arabia. In this study, the application of terrestrial light detection and ranging (LiDAR) technology was applied aiming to propose a strategy to analyze and accurately depict the detection of rockfall changes, calculation of rockfall volume, and evaluate rockfall hazards along the Habs Road, Jazan Region, Saudi Arabia. A series of temporal LiDAR scans were acquired at three selected sites. Our results show that these three sites have different degrees of hazard due to their geological differences. The mean volume loss of sites A1, A2, and A3 is 327.1, 424.4, and 3.7 L, respectively. Statistical analysis confirms the significance of the influence of site type on rockfall volume, with a probability value of < 0.0105. The rockfall volume and change detection values are then correlated with precipitation, which is a triggering factor. The study also reveals that the use of terrestrial LiDAR could reduce time and effort, increase accessibility, and produce effective solutions. LiDAR could be an indispensable tool for disaster risk assessment, response and recovery process.